(untitled) (African Journal of Biomedical Research, 2023)
There is a growing number of older persons globally. Geriatric Care is however evolving in Africa. This study was conducted to assess the knowledge and the attitude of nursing and medical students of the University of Ibadan, Nigeria towards the care of older persons. This is a descriptive cross-sectional study using self-administered questionnaires among 311 students comprising 258 (83%) medical students and 53 (17%) nursing students to assess their knowledge, attitude and older person’s care experience. Data were analysed using the Statistical Package for Social Sciences version 27 (SPSS-27) software. Data were summarized using frequency and percentages and presented in tables and figures. Chi-Square was used for the test of association between knowledge and attitude scores and socio-demography. The level of significance was set at 5%. The mean ages of respondents were 23.48±2.367 and 21.26±1.571 for medical students and nursing students, respectively. Majority of the respondents, 244 (94.6%) and 36 (67.9%) were older than 20 years old. Majority of Nursing 48 (90.6%) and Medical Students 201 (77.9%) had poor knowledge of caring for older persons. However, more than two thirds 34 (64.2%) and 173 (67.1%) of the medical and nursing students respectively, had a good attitude towards the care of older persons. More female medical 32 (26.2%), and nursing students 5 (10.4%) had good knowledge compared to their male colleagues (25, 18.4%), (0, 0.0%). (p= 1.000). Majority of medical and nursing students at the University of Ibadan, Nigeria have limited knowledge but a good attitude towards the care of older people. Hence, there is a need to include geriatrics-specific courses into their training curriculum